Intellectual capital and corporate performance: The role of controlling shareholders among Taiwanese semiconductor firms - Asif, Jawad; Irene, Wei Kiong Ting; Qian, Long Kweh (2019)
This study aims to examine how controlling shareholders would influence the level of intellectual capital (IC), which would ultimately affect corporate performance. This study applies data envelopment analysis to measure corporate performance and utilizes a modified model of Value Added Intellectual Capital (VAICTM) to measure the levels of IC of 132 semiconductor firms that are listed in Taiwan for the years 2008–2017. Regression analyses are employed to assess how the level of shareholdings by controlling shareholders would affect the level of IC, as well as the effect of IC on corporate performance. Empirical results show that companies with controlling shareholders having higher levels of shareholdings have higher levels of IC. This test-of-difference is also confirmed in our regression analyses, whereby the level of shareholdings by controlling shareholders positively affects the level of IC. However, only two components of VAICTM, namely human capital and physical capital, positively affect corporate performance. An overly high level of structural capital may mean lower scale efficiency. When examining IC, its cause and effect should be simultaneously considered. For example, controlling shareholders might have invested in intangible resources for their best possible corporate performance. Besides, as there are various criticisms of VAICTM, cautions should be exercised. The results of the study can help policy makers and other stakeholders to understand the role of controlling shareholders in investing in intellectual capital and its further impact on corporate performance. According to the resourcebased view, more useful resources would mean better corporate performance. This study provides an extended perspective in studies related to intellectual capital and corporate performance by considering resources brought by controlling shareholders.